Introduction to industrial design and product case studies - Siegkas, Petros (My University, 2021)
This paper describes the practical elements included in the first term of a second-year engineering module which was developed in alignment with CDIO standards. The students were assigned into teams based on their course of study (i.e. electronics, biomedical, and sports engineering). Each team would be free to choose, research, and evaluate three products with some relevance to their field. Aspects such as technology, regulations and user reviews would have to be considered within the analysis. The scientific principles involved in the products would have to be explained in reasonable depth and aspects such as product end-of-life management (sustainability) also mentioned. Multiple sources would have to be used such as scientific articles, product specifications, regulations, and online reviews. The students would have to use available resources without necessarily having the actual physical product at hand. Once the teams had gained insight on the products they would have to either choose one of the products to improve, or decide to design a new product, (relevant to their discipline). The teams would have to produce a report and a demonstrator of their designs by the end of term. The demonstrator would have to be a physical representation with some functionality that can effectively communicate the proposed concept. The students were expected to use the tools and experience gained during previous and prerequisite modules, for designing and prototyping. The report was also expected to contain references to the indicative reading. The module would be an opportunity to build upon previous knowledge obtained through both, core and specialized modules. Additionally, a research element was included both in terms of the students looking into the cutting-edge technologies of their subject but also in trying to push those boundaries. This study aims at describing the module rationale, and reflecting upon inclusivity, and pedagogical effectiveness.
Keywords: Group projects; industrial design; innovation; Standards: 1, 2, 3, 5, 7, 8